2011
DOI: 10.1002/jcb.23350
|View full text |Cite
|
Sign up to set email alerts
|

The wnt/β‐catenin signaling pathway: A potential therapeutic target in the treatment of triple negative breast cancer

Abstract: Breast cancer continues to be a serious health problem particularly in developed countries. Of particular concern is triple negative breast cancer (TNBC) which does not respond well to standard hormone therapy and is associated with poor overall patient prognosis. Recent studies indicate that Wnt/β-catenin signaling is particularly activated in TNBC, such that the Wnt receptor frizzled-7 (FZD7) and the Wnt co-receptor LRP6 were found to be up regulated in TNBC. In addition, it has been demonstrated that transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
190
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 253 publications
(196 citation statements)
references
References 48 publications
6
190
0
Order By: Relevance
“…The IGF-1 signaling may play a less prominent role in MDA-MB-231 cells (44), and other signaling pathways, including Wnt signaling, are important mediators of tumorigenesis in these cells. As klotho is a potent inhibitor of Wnt signaling in other malignancies, it is possible that some of its effects in breast cancer are mediating by affecting Wnt signaling (37,46). Several studies demonstrated a critical role for residues within klotho's putative active site in mediating some of the activities of klotho.…”
Section: Discussionmentioning
confidence: 99%
“…The IGF-1 signaling may play a less prominent role in MDA-MB-231 cells (44), and other signaling pathways, including Wnt signaling, are important mediators of tumorigenesis in these cells. As klotho is a potent inhibitor of Wnt signaling in other malignancies, it is possible that some of its effects in breast cancer are mediating by affecting Wnt signaling (37,46). Several studies demonstrated a critical role for residues within klotho's putative active site in mediating some of the activities of klotho.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the transcriptional knockdown of FZD7 or LRP6 in triple-negative breast cancer cells represses tumor growth (Jamdade et al, 2015). Accumulating evidence demonstrated that activated Wnt/ -catenin signaling participates in the pathological process of breast cancer (King et al, 2012;Lu and Li, 2014;Ma et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Fzd receptors overexpression has a strong correlation with tumor progression and are also expressed in HER2 negative breast cancer cell lines. 46 As Wnt targeting is a new candidate for breast cancer immunotherapy, anti-Fzd7 antibodies could be new alternatives in this regard.…”
Section: Discussionmentioning
confidence: 99%